1978
DOI: 10.1021/bi00607a035
|View full text |Cite
|
Sign up to set email alerts
|

Coat protein binds to the 3'-terminal part of RNA 4 of alfalfa mosaic virus

Abstract: All four RNAs of alfalfa mosaic virus contain a limited number of sites with a high affinity for coat protein [Van Boxsel, J. A. M. (1976), Ph.D. Thesis, University of Leiden]. In order to localize these sites in the viral RNAs, RNA 4 Tthe subgenomic messenger for coat protein) was subjected to a very mild digestion with ribonucleast T1. The ten major fragments, apparently resulting from five preferential hits, were separated and tested for messenger activity in a wheat germ cell-free system, as well as for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…4, B and C). A transition from a more flexible to a more constrained 3´ end upon CP binding agrees with a replication model suggesting that an RNA conformational change accompanies CP binding to the 3´ ends of the genomic RNAs (25). Circular dichroism analyses and polyacrylamide gel electrophoresis experiments also suggest that the AMV 3 UTR RNA becomes more compact in the presence of CP (11,17).…”
supporting
confidence: 78%
“…4, B and C). A transition from a more flexible to a more constrained 3´ end upon CP binding agrees with a replication model suggesting that an RNA conformational change accompanies CP binding to the 3´ ends of the genomic RNAs (25). Circular dichroism analyses and polyacrylamide gel electrophoresis experiments also suggest that the AMV 3 UTR RNA becomes more compact in the presence of CP (11,17).…”
supporting
confidence: 78%
“…It was first proposed by Houwing and Jaspars that an RNA conformational change accompanies CP binding to the 3Ј ends of the genomic RNAs and thereby presents a recognition signal for replicase binding (20). Results from circular dichroism analyses and native polyacrylamide gel electrophoresis experiments support the idea that the 3Ј untranslated region (UTR) of AMV RNA3 and -4 undergoes a conformational change upon binding amino-terminal CP peptides (3).…”
Section: Alfalfa Mosaic Virus (Amv) and Ilarvirusmentioning
confidence: 94%
“…The viral CP is translated from a subgenomic RNA4, which is generated by the internal initiation of transcription from minus-strand RNA3. In vitro-transcribed RNA4 (CP mRNA) can substitute for CP in the activation of replication when inoculated with the genomic RNAs into tobacco protoplasts (46).It was first proposed by Houwing and Jaspars that an RNA conformational change accompanies CP binding to the 3Ј ends of the genomic RNAs and thereby presents a recognition signal for replicase binding (20). Results from circular dichroism analyses and native polyacrylamide gel electrophoresis experiments support the idea that the 3Ј untranslated region (UTR) of AMV RNA3 and -4 undergoes a conformational change upon binding amino-terminal CP peptides (3).…”
mentioning
confidence: 99%
“…The observation that AlMV RNAs are able to withdraw CP subunits from virus particles in vitro indicated that the RNAs contain specific binding sites with a high affinity for CP (10). In subgenomic RNA 4, which is identical in sequence to the 3′-terminal sequence of 881 nucleotides (nt) of RNA 3, these high-affinity binding sites were predominantly localized in the 3′-terminal untranslated region (UTR) (11). The 3′-terminal 145 nt of RNAs 1, 2 and 3 show a sequence similarity of 80% and despite the nucleotide differences in these sequences, all termini can be folded into a similar secondary structure (12).…”
Section: Introductionmentioning
confidence: 99%